A produção integrada de maçã frente às exigências do mercado internacional de frutas - Denicol Júnior, Sílvio (My University, 2014)
The increasing demand for quality and safe food is been pushing the agri-food chains to adopt alternative production systems, with the purpose of generate healthy and innocuous products for human consumption through traceable practices, in order to protect the environment, workers and consumer. The integrated apple production (PIM) has emerged as a response to these requirements, serving as a tool to standardize the production of this fruit. From this, the study examined whether the adoption of pim in apple production chain, it is enough to avoid that this product being a subject for technical and non-tariff barriers in the foreign market. Considering this, it was researched which apple certifications are more relevant to the consumer markets, looking for identifying and classifying the requirements and also which is the positioning of the pim considering this kind of regulations. Therefore, was developted an exploratory study, through a bibliografic, documental and survey research inside the PIM, from which it was possible identify that the PIM requires adjustments to maintain its relevance as a certification in the apple productive chain, because it still does not have the equalization to the international labels, that is required to its acceptance on abroad, or even the recognition in the domestic market
As crescentes exigências por qualidade e demanda a alimentos seguros pressionam as cadeias agroalimentares, para que adotem sistemas produtivos alternativos, e que estes gerem produtos saudáveis e inócuos ao consumo humano, por meio de práticas rastreáveis, visando à proteção do meio ambiente, dos trabalhadores e dos consumidores. A Produção Integrada de Maçã (PIM) surgiu como uma resposta a essas exigências, atuando como uma ferramenta de padronização da produção dessa fruta. A partir disso, o trabalho verificou se a adoção da PIM, na cadeia produtiva de maçã, é suficiente para que esse produto não esteja sujeito a barreiras técnicas e não tarifárias do mercado externo. Para isso, foram pesquisadas quais certificações para maçã são mais relevantes aos mercados consumidores, buscando identificar e classificar os requisitos e qual o posicionamento da PIM perante essas regulamentações. Para tanto, foi desenvolvido um estudo exploratório, por meio de pesquisa bibliográfica, documental e de levantamento dentro da PIM, pelo qual foi possível identificar que necessidade de ajustes para que esse programa mantenha sua relevância como certificação na cadeia produtiva da maçã, pois não possui a equiparação aos selos internacionais, necessária para sua aceitação no Exterior e nem conhecimento no mercado nacional.
Keywords: Administração; Produção integrada de maçãs; Cadeia produtiva; Certificação; Produtividade agrícola; Controle de qualidade; Administração da produção; Maçã - Cultivo; Integrated apple production; Productive chain; Certification; Agricultural productivity; Quality control; Apples - Planting